(untitled) - 1983-; Kircher, William; Brophy, Jed; Hunter, Stephen; (Actor); Pace, Lee; 1979-; Cumberbatch, Benedict; 1976-; (Actor); OGorman, Dean; McTavish, Graham; et al. (Burbank, CA, 2013)
The first chapter in Peter Jacksons new epic trilogy set in Middle Earth 60 years before J.R.R. Tolkiens Lord of the rings saga. Follow Bilbo Baggins as hes swept into a quest to reclaim the Dwarf Kingdom of Erebor, long ago conquered by the dragon Smaug. Approached by the wizard Gandalf, Bilbo joins a company of thirteen dwarves led by the legendary warrior Thorin Oakenshield. Along the way they face many dangers; Bilbo meets Gollum and takes possession of the One ring. Includes bonus features.
Keywords: Tolkien, J. R. R; 1892-1973.; Film adaptations; Baggins, Bilbo; Hobbits (Fictitious characters); Middle Earth (Imaginary place); Video recordings for the hearing impaired; Fiction films; Film adaptations; Feature films; Action and adventure films; Fantasy films